KEABSAHAN PERWALIAN TINDAKAN HUKUM ATAS JUAL BELI TANAH DENGAN PENJUAL ANAK DI BAWAH UMUR ( STUDI PENETAPAN NEGERI Nomor : 109/Pdt.P/2015/PN.Kdl) - Anzal Sabri; Vanes Sabri (Fakultas Hukum Universitas Narotama, 2022)
This study aims to determine the reason for the biological mother submitting an application for child guardianship, the basis for the judge's consideration in granting a child guardianship application, and the legal consequences after the guardianship determination. The method in this research is to use research with an empirical juridical approach, with qualitative legal research types, and the sources used are through field research. The result of this study is that the reason for the birth mother who wants to sell the Certificate of Ownership and the money is used for the needs of her child's school fees. The basis for the judge's consideration in granting this petition is based on Article 47 of Law Number 1 of 1974 concerning Marriage which states that parents can represent their children as long as their power is never revoked. And as a result of this determination there is a decision from the court that the biological mother can still represent her child legally. Keywords : Skills, Guardianship, Children